Sarah Freeland (ed.): International Recipe Book - D., J.M. (Petits Propos Culinaires, 2024)
Sarah Freeland (ed.): International Recipe Book: Diplomatic Service Wives’ Association, FCO, Curtis Green Building, Victoria Embankment, London SWJA 2JD: 108 pages, printed card cover, neatly reduced typescript within, comb binding, £1.00 (or £1.25 including p and p, surface mail to anywhere in the world).